Chinese Medical Therapies for Diabetes, Infertility, Silicosis and the Theoretical Basis - Li, Xing-Tai (IntechOpen, 2017)
Traditional Chinese medicine (TCM) is the world's most comprehensive alternative and complementary medicine. With the rising morbidity of serious illnesses like diabetes, infertility, silicosis, etc., there are no highly effective treatments; even though Western medicine has made spectacular advances, this influenced us to seek Chinese medical therapies of health care. This book offers a unique perspective of Chinese medicine theories and therapies. It has practical chapters on diabetes, infertility, silicosis, kidney essence, and a compilation of contraindicated Chinese medicines for pregnancy. TCM is a treasure, and this ancient wisdom should be respected and applied to the modern medical system; it will provide more choices and a wider field of vision for Western medicine at the two cognitive crossroads of East and West.